2014
DOI: 10.1007/s11606-014-2933-7
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Statin Compliance after Switching from Branded to Generic Agents among Managed-Care Beneficiaries

Abstract: OBJECTIVES:To identify patient demographics and characteristics associated with compliance to statin therapy after switching from branded to generic agents DESIGN: Retrospective cohort study using electronic health records and pharmacy claims data from Sutter Health's ambulatory-care medical network PATIENTS: Managed-care beneficiaries, ≥ 18 years of age, who were switched from branded to generic statins between 1 January 2003 and 31 December 2012 MAIN MEASURES: Compliance was calculated as days of therapy dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Studies of patients who switched from branded to generic atorvastatin have also shown that switching may change patients' adherence [57][58][59][60][61] (Table 1). For example, an 18-month non-interventional real-world study conducted in Greece by Tsioufis et al compared the adherence of patients who continued taking branded atorvastatin with those who switched to generic atorvastatin [58].…”
Section: Comparing Adherence and Persistence With Branded Versus Generic Atorvastatinmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of patients who switched from branded to generic atorvastatin have also shown that switching may change patients' adherence [57][58][59][60][61] (Table 1). For example, an 18-month non-interventional real-world study conducted in Greece by Tsioufis et al compared the adherence of patients who continued taking branded atorvastatin with those who switched to generic atorvastatin [58].…”
Section: Comparing Adherence and Persistence With Branded Versus Generic Atorvastatinmentioning
confidence: 99%
“…Studies of adherence among patients prescribed atorvastatin have demonstrated that the switch from branded to generic atorvastatin had a mixed impact on adherence [ 57 61 ]. For example, a 6-month retrospective study analyzed adherence in 3417 patients on statin therapy (atorvastatin, fluvastatin, lovastatin, pravastatin, simvastatin) who switched from a branded to a generic formulation [ 57 ]. Patients with a medication possession ratio (MPR; ESM Table S1) ≥ 80% were considered to be ‘adherent.’ Of those who switched from a branded to generic formulation, the majority (52.3% [ n = 1786/3417]) switched from branded to generic atorvastatin.…”
Section: Comparing Adherence and Persistence With Branded Versus Generic Atorvastatinmentioning
confidence: 99%
“…The investigators find that a majority of patients were compliant in the six months after switching. 1 Higher compliance was associated with equivalent potency to the prior branded statin and higher pre-switch compliance. 1 Lower compliance was seen among Hispanic patients.…”
mentioning
confidence: 95%
“…1 Higher compliance was associated with equivalent potency to the prior branded statin and higher pre-switch compliance. 1 Lower compliance was seen among Hispanic patients. The authors concluded that there is a potential for non-compliance to generic statin therapy, particularly among Hispanic patients or when dose/potency is increased.…”
mentioning
confidence: 95%
See 1 more Smart Citation